Јаsenovac, the Camp and its historical and moral meaning - Greif, Gideon (Napredak, 2022)
The paper gives an overview and stages of the development of the Ustasha concentration camp Jasenovac, during the existence of the “Independent State of Croatia” (ISC) in World War II. The fact is emphasized that the policy of the “Final solution” (for Jews and Romas, and in Croatia for Serbs as well), which was implemented by Nazi Germany, chronologically looking, was actually first applied in the ISC, and then in Germany. According to several criteria, the comparison is made between the concentration camps Auschwitz and Jasenovac, while particularly insisting on the brutality in the Ustasha killing of the victims in Jasenovac.